RETRACTED: The Role of Subjects in Kuntowijoyo's Transformative Thought and It's Relevance to the Prophetical Social Transformation - M. Rodinal Khair Khasri; Rizal Mustansyir (SASDAYA: Gadjah Mada Journal of Humanities, 2020)
Following a rigorous, carefully concerns, and considered review of the article published in SASDAYA: Gadjah Mada Journal of Humanities to the article entitled: The Role of Subjects in Kuntowijoyo's Transformative Thought and It's Relevance to the Prophetical Social Transformation vol 4, No. 2 2020. (pp. 126-144)DOI:  https://doi.org/10.22146/sasdayajournal.59662This paper has been found to be in violation of the SASDAYA: Gadjah Mada Journal of Humanities Publication Principles and will be retracted.The article contained double submission, redundant material, the editor investigated and found that the paper published in “The Role of Subject in Kuntowijoyo's Transformative Thought and It's Relevance to The Islamic Social Transformation” Vol 30, No 2, pp. 261-286, 2020, DOI: https://doi.org/10.22146/jf.54911 The document will be watermarked for digital tracking.